Edukasi Perilaku Hidup Bersih Dan Sehat (Phbs) Rumah Tangga Untuk Peningkatan Pengendalian Diabetes Melitus Pada Kelompok Prolanis Puskesmas Balowerti - Prima Dewi K; Elin Nurnianingsih; Moudi Putri Lestari; Nur Laili (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2026)
The high prevalence of Type 2 Diabetes Mellitus (DM) in Indonesia, particularly in Kediri City, accompanied by the still-low achievement of controlled DM and household Clean and Healthy Living Behavior (PHBS), constitutes the main background of this activity. Data from the Prolanis group at UPT Puskesmas Balowerti showed that among 35 DM participants who underwent HbA1c examination, only 54.28% had controlled blood glucose, while the household PHBS survey in the working area of the health center reached only 58.04%. This community service activity aimed to improve the knowledge, attitudes, and skills of the Prolanis group in implementing three PHBS components, namely physical activity, handwashing with soap (CTPS), and consumption of fruits and vegetables, to support achieving controlled DM. The activity was conducted on Friday, 12 June 2026 at the Hall of UPT Puskesmas Balowerti, involving 30 participants with DM, using lecture methods, a five-movement seated exercise demonstration, a six-step handwashing demonstration, question-and-answer discussion, and a quiz, evaluated through pre-test and post-test instruments and participation observation. The analytical technique used was comparison of average pre-test and post-test scores to measure improvement in participants' knowledge. The results showed a meaningful increase in knowledge, with the average pre-test score of 75.56 rising to 93.89 in the post-test (a 24.26% improvement), surpassing the minimum target of 20%. All invited participants attended and actively participated in the demonstration and quiz sessions for each PHBS component, and expressed commitment to implementing PHBS in their households. Structured PHBS education is effective in increasing the understanding and motivation of DM patients to manage their disease independently as an early stage of behavior change, and should therefore be sustained and replicated in other Prolanis groups.